2022
DOI: 10.1186/s44149-022-00057-5
|View full text |Cite
|
Sign up to set email alerts
|

Are CD45RO+ and CD45RA- genuine markers for bovine memory T cells?

Abstract: Effective vaccination induces memory T cells, which protect the host against pathogen re-infections. Therefore, detection of memory T cells is essential for evaluating vaccine efficacy, which was originally dependent on cytokine induction assays. Currently, two isoforms of CD45 tyrosine phosphatase, CD45RO expression and CD45RA exclusion (CD45RO+/ CD45RA-) are used extensively for detecting memory T cells in cattle. The CD45RO+/CD45RA- markers were first established in humans around three decades ago, and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…The consequences of the current research showed that the percentage of CD45RO + CD27 + T cells in CD4 and CD8 T cells increased significantly at 7 days after vaccination compared with pre-vaccination and returned to pre-immunization levels at 14 days. Over that past decades, numerous reports on humans and cattle have challenged the classical CD45RA/RO paradigm, which defined the memory phenotype as CD45RO + and CD45RA − cells ( 54 , 55 ). For instance, cell proliferation was not observed after stimulation of CD45RO + CD4 + and CD45RO + CD8 + T cells isolated from cattle using the homogenates of the parasites ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of the current research showed that the percentage of CD45RO + CD27 + T cells in CD4 and CD8 T cells increased significantly at 7 days after vaccination compared with pre-vaccination and returned to pre-immunization levels at 14 days. Over that past decades, numerous reports on humans and cattle have challenged the classical CD45RA/RO paradigm, which defined the memory phenotype as CD45RO + and CD45RA − cells ( 54 , 55 ). For instance, cell proliferation was not observed after stimulation of CD45RO + CD4 + and CD45RO + CD8 + T cells isolated from cattle using the homogenates of the parasites ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…The single-cell suspension obtained was subjected to cell counting and antibody staining. Peripheral blood mononuclear cells (PBMCs) were similarly performed as in our previous reports [ 130 , 131 , 132 ]. Blood was collected from the jugular vein using EDTA-coated vacutainers (Becton Dickinson Vacutainer Systems, Franklin Lakes, NJ, USA) and transferred to 15 mL conical containers (Fisher Scientific, Pittsburgh, PA, USA), which were centrifuged at 1200× g -force (G) for 30 min.…”
Section: Methodsmentioning
confidence: 99%